Effective bending and shear stiffness of cross-laminated timber by modal testing: Method development and application. (1st October 2020) - Zhou, Jianhui; Chui, Ying Hei; Niederwestberg, Jan; Gong, Meng
Abstract: Cross-laminated timber (CLT) is gaining popularity worldwide with the development of tall wood buildings. A non-destructive testing (NDT) technique employing modal testing for the measurement of natural frequencies and a genetic algorithm for minimizing the difference between calculated and measured natural frequencies has been proposed for the inverse determination of in-plane and out-of-plane elastic constants of orthotropic Mindlin plates. Based on the exact solution of free transverse vibration of orthotropic Mindlin plates under a pair of opposite edges simply supported and the other pair free (SFSF), the effective bending and shear stiffness of two three-layer and one five-layer symmetric CLT panels were inversely determined. Moreover, the results showed that the inclusion of five sensitive vibration modes was more efficient than having more modes for the inverse determination. This study demonstrated the efficiency and potential of the non-destructive method in measuring the effective bending and shear stiffness of mass timber panels.